Simulation Study on the Surface Texturing Design of COC Hip Joints Based on Elastohydrodynamic Lubrication Model - Zhenxing Wu; Leiming Gao; Xiuling Huang; Zikai Hua (Lubricants)
Post-operative feedback from hip replacement surgeries indicates that implanted ceramic artificial hip joints may produce abnormal noises during movement. This occurrence of joint noise is highly correlated with insufficient lubrication of ceramic-on-ceramic (COC) prostheses. Studies have shown that surface texture design can improve lubrication performance. In this study, the elastohydrodynamic lubrication model was established with designing textures on the surface of the COC hip joint, using Matlab R2018b and GNU FORTRAN in Codeblocks 20.03 programming. Iterative calculations were performed to determine the average bearing capacity of the oil film and the friction coefficient. The study explored the impact of texture parameters, including the aspect ratio and density, on the lubrication and friction performance of the hip joints. The results indicate that the textured surface generally has a higher fluid film bearing capacity by 161.5~637.7% and a lower friction coefficient by 10.7~60% than the smooth surface. The average bearing capacity of the fluid film increases with an increasing texture aspect ratio, while the trend of the friction coefficient is identical to the average bearing capacity results. As the texture density increases, the average bearing capacity of the fluid film first decreases and then increases, and the trend of the friction coefficient also increases accordingly. Among the nine design groups (<semantics>Sp=0.05,0.15,0.35,ε=0.075,0.1,0.15</semantics>), based on the fuzzy comprehensive evaluation, the local optimal solution is <semantics>Sp=0.15</semantics>, <semantics>ε=0.075</semantics> for lubrication and wear resistance.